Thermophysical, and rheological insights of polyethylene/wax blends - Mhlabeni, Thobile L.; Jamiru, Tamba; Mhike, Washington (Frontiers in Chemical Engineering, 2024)
Blending wax with polyethylene (PE) has garnered significant attention in recent years due to its potential to enhance processing capabilities of polyethylene-based products. The miscibility of polyethylene and low molecular mass wax blends is a critical factor influencing various industrial applications. In this study, the theoretical framework of the miscibility of polyethylene/wax blends is discussed in terms of thermodynamic principles. The state-of-the-art of miscibility of polyethylene/wax blends is comprehensively examined, focusing on their thermophysical and rheological properties. It is shown that thermophysical properties assessed by differential scanning calorimetry and dynamic mechanical analysis can provide insights into thermal transitions affected by blend composition. Furthermore, the rheological properties of blends can provide insights into their microstructure, phase behaviour, and interaction between components. Literature search of the influence of wax compositions and temperature on the polyethene/wax compatibility was shown to be inconsistent. Also, studies on the miscibility of paraffin and Fischer-Tropsch (F-T) wax/polyethene blends is limited. However, the review suggests full miscibility of low molecular mass waxes and polyethylene in the melt and partial co-crystallisation in the solid state.